Magnesium-doped zircon-type rare-earth orthovanadates: Structural and electrical characterization. Issue 1 (January 2018) - Gayathri, T.H.; Yaremchenko, A.A.; Macías, J.; Abhilash, P.; Ananthakumar, S.
Abstract: Undoped LnVO4 and magnesium-doped Ln0.95 V0.95 Mg0.10 O4-δ (Ln = Pr, Sm, Gd, Dy and Er) orthovanadates were synthesized by solid state reaction method and characterized by XRD, SEM/EDS, electrical conductivity measurements in controlled atmospheres, and modified e.m.f. technique for determination of oxygen-ion transference numbers. XRD analysis showed the formation of phase-pure materials with tetragonal zircon-type structure and a decrease in lattice parameters with a decrease of ionic radius of rare-earth cations. Trace amounts of MgO and Mg-V-O phases revealed by SEM/EDS suggest that the solid solubility limit of magnesium cations in LnVO4 lattice is somewhat lower than the nominal doping level, and that magnesium substitutes preferentially into the vanadium sublattice. LnVO4 and Ln0.95 V0.95 Mg0.10 O4-δ orthovanadates show semiconducting behavior under oxidizing conditions at 450–950 °C and are predominantly oxygen-ionic conductors, except PrVO4 that shows mixed conductivity. In the LnVO4 series, electrical conductivity is the highest for PrVO4 and SmVO4 ( 4 × 10 −4 S/cm at 800 °C) and decreases with increasing atomic number of rare-earth cation for the other compositions. Additions of magnesium results in a drop of electrical conductivity, by 1.5–2 times for most of compositions. Interstitial oxygen diffusion is discussed as a prevailing mechanism of ionic transport in undoped LnVO4, whilst acceptor-type magnesium doping suppresses the formation of interstitial oxygen ions. Humidity has a rather negligible impact on the electrical properties of substituted ceramics, indicating only minor (if any) protonic contribution to the total electrical transport of the studied orthovanadates.